Vejo logo simbolizo! Uma abordagem semiótica da percepção da linguagem visual - Campanhole, Sidney Gomes (2006)
The present work has as its objective the study of the perceptive apprehensions of visual language, which in this case is the one systematized in the classroom. Starting from the epistemology of the Peircean Semiotics, one proposes to review the discussion between innatists and empiricists on perception, which from Philosophy extends to Psychology in the 20th century. It places the source of systematized learning in the classroom and takes perception as tangible matter in the language produced. The perceptive development perspectives implicit in the evolution of the Visual Arts and children s drawing are analyzed synthetically for verification of congruence points. The profile regarding school praxis, observed as language, allows verifying its accommodation in the area of Art education and submission to non-verbal language classifications. The study seeks to question the innate question, the gift, that the paths of school praxis and the cultural environment restrict visual language. It proposes to subsidize future discussions on qualitative relations in the phenomenon of Communication, from a more qualitative apprehension of its language. Given the sign-perception focus, and consequently, language-cognition, one seeks to compare the idiosyncratic visions of visual language acquisition. For this purpose, it dialogues with the theory of multiple intelligences that reinforces the interaction between medium and genetic determinism. The main hypothesis is the displacement of existing learning activities, or in case they are not existent, then those to be developed from the predominance of the third category must dislocate to the second category, that is, from apprehension of legi-signs for the sin-sign. The visual language to be learned required the definition of the aspects of syntax and morphology, given that for such a dialogue was articulated between the principles of ordination of perceptive structures proposed by Gestalt and its variations. The experimental character of the research fell into groups of students of two segments of the school system, whose verifications did not establish relation between them, taking as variable the before-after of each group. One submitted to the apprehension of morphology and the other to syntax. The conclusion based on the research states that perception occurs at the moment and in a mediated way. As long as the first one might produce reorganizations of the sign at the duration of the process of keeping , the second one tends to generate associating processes that, in fact, make the relations with the object analised distant from its existence, limitating the visual language learning